mHealth Technologies for Managing Problematic Pornography Use: A Content Analysis - Henry, N (AUTSA, GRS and Tuwhera Open Access, 2022)
Approximately one in twenty individuals struggle with Problematic Pornography Use (PPU) (Bőthe et al., 2020). Several mobile apps are currently available that claim to help with managing ‘pornography addiction'. However, the utility of these apps is unclear, given the lack of literature on the effectiveness of mHealth solutions for PPU. Hence, this study aims to characterize the purpose, content, and popularity of mobile apps that claim to manage pornography addiction. This analysis includes 170 apps for both Android and iOS that meet the inclusion criteria. The five most common and popular features are: the ability to track the time since last relapse, tutorials and coaching, access to accountability partners or communities, content blocking or content monitoring, and a reward system for progress. Of these features, content blocking apps have the highest total number of users, but also have the lowest mean consumer satisfaction rating out of five stars. None of these apps contain references to literature providing evidence for their efficacy or safety. In conclusion, there are several apps with the potential to provide low- or zero-cost, real-time interventions for people struggling to manage PPU. In particular, content blocking apps show some promise for PPU management. However, there is currently no empirical evidence to support the effectiveness and safety of these apps. Further research is required to be able to recommend apps that are safe for public consumption.
Keywords: Pornography; Problematic Pornography Use (PPU); Mobile interventions